The shape shifter - Hillerman, Tony (HarperCollins, 2006)
"Retired from the Navajo Tribal Police, Lieutenant Joe Leaphorn is called upon once again to solve a crime. This time it's Joe's last case, a case that remains unsolved and contines to haunt him."--From source other than the Library of Congress